Experimental determination and numerical prediction of necking and fracture forming limit curves of laminated Al/Cu sheets using a damage plasticity model. (April 2019) - Zahedi, Ali; Mollaei Dariani, Bijan; Mirnia, Mohammad Javad
Highlights: The modified Xue–Wierzbicki plasticity damage model is employed for obtaining fracture forming limit strains of laminated aluminum/copper sheets. Effects of lode parameter and hydrostatic pressure are being explored on the fracture forming limit strains. Necking forming limit strains of laminated sheets is calculated based on a time-dependent necking criterion and validated with the experimental results. The influence rule of the lay-up arrangement on the fracture and necking limiting strains is presented in details. Abstract: Different mechanical, physical and chemical properties such as high strength-low weight structures, good corrosion resistance and appropriate thermal and electrical conductivity of multi-layer sheet metals have increased their applications in industry and research community. In this study, the forming behavior of a two-layer metal sheet during the hemispherical punch stretching test is investigated. The laminated sheet is fabricated from the AA1050 aluminum and 1100 copper sheets using the explosive welding. Various geometries of the laminated sheet for two different lay-ups are utilized to induce different stress states during the hemispherical punch stretching test. By measuring the strain pairs of the fractured specimens, the necking forming limit curve (NFLC) and the fracture forming limit curve (FFLC) of the two-layer sheet are experimentally achieved. In order to numerically predict limiting strains at the necking and fracture initiation, a time-dependent method and the modified Xue–Wierzbicki damage plasticity model incorporating effects of the hydrostatic pressure and the Lode angle parameter are respectively employed in the Abaqus/Explicit finite element (FE) code using the user subroutine VUMAT. It is shown that using a hybrid numerical-experimental approach, both the NFLC and FFLC of the Al/Cu two-layer sheet can be well predicted. Using the damage model, the participation of effective factors at the onset of fracture is described and it is experimentally shown that cracks begin to initiate and propagate from the outer layer. Results also show that the Al/Cu two-layer sheet would have a higher fracture and necking limiting strains when the punch comes into contact with the inner aluminum layer. Graphical abstract: Image, graphical abstract